2022
DOI: 10.1002/smll.202107652
|View full text |Cite
|
Sign up to set email alerts
|

2D Materials and Primary Human Dendritic Cells: A Comparative Cytotoxicity Study

Abstract: Human health can be affected by materials indirectly through exposure to the environment or directly through close contact and uptake. With the ever‐growing use of 2D materials in many applications such as electronics, medical therapeutics, molecular sensing, and energy storage, it has become more pertinent to investigate their impact on the immune system. Dendritic cells (DCs) are highly important, considering their role as the main link between the innate and the adaptive immune system. By using primary huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 101 publications
(123 reference statements)
0
22
0
Order By: Relevance
“…Moreover, unlike hBN, MoS 2 did not show any effect on DC maturation, and had little effect on DC-induced T cell proliferation (Figure ). In contrast, using murine bone marrow-derived DCs as a model, other investigators have observed DC maturation at a relatively high dose (128 μg/mL) of MoS 2 . Interestingly, the in vivo homing of DCs was also enhanced upon exposure to MoS 2 .…”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unlike hBN, MoS 2 did not show any effect on DC maturation, and had little effect on DC-induced T cell proliferation (Figure ). In contrast, using murine bone marrow-derived DCs as a model, other investigators have observed DC maturation at a relatively high dose (128 μg/mL) of MoS 2 . Interestingly, the in vivo homing of DCs was also enhanced upon exposure to MoS 2 .…”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
“…Comparative study of hexagonal boron nitride (hBN), graphene oxide (GO), and MoS 2 using primary human monocyte-derived dendritic cells (DCs). Transmission electron microscopy (TEM) micrographs of DCs maintained in medium along (Control) or exposed to 50 μg/mL hBN, GO, or MoS 2 for 24 h. The stars indicate the localization of the materials . Reproduced with permission from Lin, H.; Peng, S.; Guo, S.; Ma, B.; Lucherelli, M. A.; Royer, C.; Ippolito, S.; Samori, P.; Bianco, A.…”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
“…130 This procedure was later used with the addition of bile salts in the exfoliation process to study the cytotoxicity of hBN in human dendritic cells, showing that hBN has minimal toxicity on dendritic cell viability. 131 A study in 2018 by Wang and coworkers compared ionic and nonionic surfactants for hBN dispersion, concentration, and stability in alkaline environments with the goal of using hBN to enhance Portland cement paste. 13 Here, they found that addition of the ionic surfactant SDS or nonionic surfactants PC or GA reduced the dispersion concentration compared to water alone.…”
Section: Ionic Surfactantsmentioning
confidence: 99%
“…130 This procedure was later used with the addition of bile salts in the exfoliation process to study the cytotoxicity of hBN in human dendritic cells, showing that hBN has minimal toxicity on dendritic cell viability. 131…”
Section: Surfactants and Polymersmentioning
confidence: 99%
“…Subsequent cultivation with T-cells confirmed the formation of large clusters of DC-GO-T-cells, thus augmentation of T-cell activation [ 149 ]. Similarly, large GO induced maturation of human monocyte-derived DC via increased expression of costimulatory molecules CD80 and CD83 [ 150 ]. Compared to that, PEGylated GO with diameters under 200 nm inhibited expression of CD83 in human DC [ 151 ].…”
Section: Modulationmentioning
confidence: 99%